PROBLEMS OF ENSURING THE INTEGRATION OF CLOUD TECHNOLOGIES IN FORMING A DATABASE FOR MOBILE APPLICATIONS - Jurayev, Tuychi; Safarov, Laziz (Techscience uz - Topical Issues of Technical Sciences, 2025)
Mobile applications have become an integral part of the modern digital world. For their efficient operation, it is essential to store and process data in a reliable, secure, and fast manner. The article examines the problems and solutions related to ensuring the integration of cloud technologies in the formation of databases for mobile applications, as well as presents practical examples from existing mobile learning applications.